Histological changes in gonads of rock sole Lepidopsetta polyxystra during its life cycle - Anna Yu. Dubinina; Alexander O. Zolotov (Известия ТИНРО, 2017)
Gametogenesis of rock sole Lepidopsetta polyxystra and its annual cycle of reproduction are described in details. In the reproductive cycle, gonads of its males and females pass a number of stages characterized by certain qualitative and quantitative composition of sexual cells, their sizes, and the size, weight and structure of sexual glands. Detailed description of all these stages is presented on anatomic, microscopic and histological levels. Stage II (immature) - gonads have small size, their anatomic differentiation is completed, sexual accessory is distinct, female gonads have predominantly unyolked oocytes with various degree of development. Stage III (maturing) - gonads are increased in volume and well appreciable, female gonads are basically filled with unyolked oocytes but have a portion of yolked oocytes maturing to forthcoming spawning, spermatogenesis in male gonads becomes more active. Stage IV (prespawning) - active accumulation of yolk in female gonads, spermatogenesis in male gonads is finished. Stage V (spawning) - gonads achieve their maximal sizes, mature oocytes after hydration move into ovarial cavity in female gonads, streams of sperm are clearly allocated on histological cuts of male gonads. Stage VI (postspawning) - gonads are flabby with a number of hematomas, female gonads tissue includes unyolked oocytes of following generation, postovulatory follicles and atretic cells, new generation of sexual cells forms in male gonads. On results of the histological analysis, a separate stage II-III is proposed for mature first-spawning females of rock sole, which will not spawn in the next year. Each set of the histological features of gonads corresponds to their certain external condition, easy diagnosed visually. The described signs can be generalized in the maturity scale for rock sole.